ILRI's Animal Health Improvement Programme (AHIP) - Irvin, T. (International Livestock Research Institute, 1998)
The contribution of livestock to the productivity and sustainability of smallholder farming systems can be severely compromised by ill health and diseases. However, disease is only one of the constraints which limit productivity in such systems. This means that improving animal health must form part of a strategy within which appropriate attention must also be given to improving management, nutrition and breeding in an integrated way. It is unlikely that any one intervention on its own will result in sustainable improvements. Improving animal health must also adopt an integrated approach which includes genetic improvement, improved management, chemotherapy, vaccination, vector control and diagnosis. Understanding the epidemiology of diseases in different farming systems will enable a correct balance of these interventions to be developed which are appropriate to different diseases and situations. This paper discusses the current research within the Animal Health Improvement Programme (AHIP), and looks in to the potential role for the AHIP listing considerations in the identification and prioritisation of the complementary areas.